THE INTERRELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND EARNINGS MANAGEMENT: FEMALE AND INDEPENDENT DIRECTORS AS MODERATORS - Anita, Anita; Hadianto, Isabela (Global Financial Accounting Journal, 2025)
Purpose - Financial reports are strategic tools; however, financial information is vulnerable to manipulation. In recent decades, the phenomenon of corporate sustainability reporting has prompted numerous studies on its impact on earnings quality, particularly where managers may use accrual flexibility to present financial reports. This study aims to determine whether corporate social responsibility (CSR) has an opportunistic perspective that influences earnings management and/or vice versa. Additionally, it examines whether female directors and independent directors affect this reciprocal relationship. Research Method - This study employs panel data regression using a sample of companies listed on the Indonesia Stock Exchange that consistently published sustainability reports for five consecutive years. Data were collected and analyzed using Eviews software, with descriptive statistics generated to provide an overview before regression testing. Findings - The regression test results indicate that the presence of independent directors moderates the relationship between CSR and earnings management practices. This demonstrates that independent directors reflect effective governance, thereby reducing agency costs. Implication - Independent directors help mitigate the opportunistic use of CSR for earnings management, promoting ethical and transparent corporate practices. This highlights the importance of prioritizing independent directors on boards to enhance governance quality and build stakeholder trust.